Geometric, optical and thermal analysis for solar parabolic trough concentrator efficiency improvement using the Photogrammetry technique under semi-arid climate. (January 2019) - Ydrissi, Massaab El; Ghennioui, Hicham; Bennouna, El Ghali; Farid, Abdi
Abstract: The investment of renewable energy, especially the solar energy, seems to be the real alternative and the potential solutions for the classical fuel energy due to its pollutant and limited source. Therefore, the cost and performance are the main criteria to assess a solar power plant. The purpose of this work is to evaluate the optical and thermal efficiencies of a solar Parabolic Trough Concentrated (PTC) installed in the Green Energy Park (GEP) research platform in Benguerir, Morocco. In order to improve the optical efficiency of the system, an optical qualification is necessary because of the difficulties of handling the glasses and the deformations from the ideal design. In this sense, an experimental study was carried out using the robust Photogrammetry measurement technique to perform the geometrical and optical errors of the solar concentrating system. Slope error, misalignment error, and receiver position error has been identified and analyzed. Moreover, the intercept factor and the optical efficiency of the PTC system according to the experimental measurements given by the Photogrammetry technique were determined. Finally, the thermal efficiency of the PTC according to results obtained and the weather conditions climate of Benguerir city extracted by an accurate meteorological station have been performed and analyzed. The results obtained show the relevant impact of the optical efficiency on the thermal energy and the plant performance.